Differences in the isokinetic strength of thigh muscles between track and field and taekwondo athletes - Tan, Y. (Frontiers in Sport Research, 2020)
This research aimed to determine the isokinetic strength differences between two groups of athletes (Taekwondo and track-and-field athletics) and to analyse factors that possibly contribute to the differences. We examined possible differences in peak power output and power ratio between agonist and antagonist thigh muscles of the knee. The sample consisted of 20 respondents: Taekwondo athletes (n=10; age 19±2.4) and track-and-field athletes (n=10; age 18±2.6). For this study, a valid test (CV<5%) of the isokinetic strength output of the knee extensors and flexors, was used at the angular velocity of 60°/s.